"I Can Do Anything if I've Overcome That": A Collaborative Case Study of an Adolescent with Symptoms of Lyme Disease in Canada - Sarah Ciotti; Shannon A. Moore; Christine Tardif-Williams (MDPI AG, 2023)
This qualitative case study explored the experiences of one Canadian adolescent with symptom-persistent Lyme disease. Lyme disease is the most prevalent vector-borne illness in North America, and infection rates are rising across Canada. Peak incidence occurs in children aged 5-9 years, making it a significant childhood infectious disease. This involves collaboration with an adolescent with symptom-persistent Lyme disease in Canada to address a gap in the literature. This empirical research was guided by the central research question: "What is the experience of an adolescent with symptom-persistent Lyme disease in Canada?" The purpose of this study was to understand the unique experiences of symptom-persistent Lyme disease in Canada by emphasizing one adolescent's unique voice. The findings of this case study demonstrate the challenges this adolescent faced in receiving appropriate diagnosis and treatment for Lyme disease, pointing to a need for increased awareness among health professionals regarding the impact and prevalence of tick-borne illnesses for young people, their caregivers, and their healthcare providers. Additional findings suggest that collaborative healthcare may be beneficial for patients with symptom-persistent Lyme disease, and health researchers should continue to engage young people to ensure accurate representation of their experiences.